Environmental aging alters Al(OH)3 coating of TiO2 nanoparticles enhancing their photocatalytic and phototoxic activities. Issue 3 (20th May 2016) - Al-Abed, Souhail R.; Virkutyte, Jurate; Ortenzio, Jayna N. R.; McCarrick, Robert M.; Degn, Laura L.; Zucker, Robert; Coates, Najwa Haykal; Childs, Kristin; Ma, Hongbo; Diamond, Steve; Dreher, Kevin; Boyes, William K.
Abstract : Environmental aging of Al(OH)3 ·TiO2 degrades the protective Al(OH)3 coating and alters the activity of the material. Abstract : As a component of sunscreen formulations, TiO2 engineered nanomaterials (ENM) are coated to prevent reactive oxygen species from causing damage to skin. We investigated the stability of an Al(OH)3 coating by exposing 25 nm Al(OH)3 ·TiO2 ENM to simulated swimming pool water (SPW) for 45 minutes, 1, 3, 10, or 14 days. Electron microscopy and spectroscopy indicated that exposure to SPW caused a redistribution of the Al(OH)3 coating allowing photocatalytic formation of hydroxyl radicals. Aged ENM showed significantly greater phototoxicity under UVA irradiation than un-aged ENM in a human-derived retinal pigment epithelium cell line (ARPE-19). Photocatalytic activity and phototoxicity of aged Al(OH)3 ·TiO2 was significantly less than that of the positive control—uncoated P25 TiO2 . In summary, the aging of Al(OH)3 ·TiO2 ENM in SPW redistributed the coating and reduced its protective properties, thereby increasing reactivity and potential phototoxicity.